The Shelf Life of Tomato Fruits (Solanum lycopersicum L.) Treated with Extracts of Two Medicinal Plants: Azadirachta indica and Vernonia amygdalina - Okolo, J. C.; Igborgbor, J. C.; Eze, E. M.; Ogu, G. I.; Jonah, G. U. (International Journal of Environment, 2022)
Tomato remains one of the most nutritive edible berries but challenged by incessant attack and spoilage by fungi among others. The negative effects of synthetic preservatives have shifted attention to bio-preservatives. This study investigated the shelf-life of post-harvest tomato fruits treated with the two medicinal plants: Azadirachta indica (neem leaf) and Vernonia amygdalina (bitter leaf) extracts. Fresh tomato fruits and leaves of both plants were sourced from Lokoja. The leaves were air-dried, pulverized and extracted with distilled water and absolute ethanol. The extracts were analyzed phytochemically and graded concentrations (2.5 g/mL - 10.0 g/mL) were applied to the tomato samples in five replications each. Weight loss, appearance of fungal mycelia and deteriorations on the tomato samples were monitored for 30 days. Fungal isolates from the deteriorated samples were recovered and subjected to in vitro inhibitory activities. Alkaloids, glycosides, saponins, flavonoids and tannins were present in both extracts, except for A. indica, where saponins was not detected. Both extracts significantly (p0.05) from each other. These findings suggest that relatively higher concentrations of both plant extracts could be potential bio-preservatives to extend the shelf life of post-harvest tomatoes.